Forensic anthropology : theoretical framework and scientific basis - Boyd, C. Clifford, Jr., 1952-; Boyd, Donna, 1960- (Hoboken, NJ : Wiley, 2018)
'Provides comprehensive coverage of everything that students and practitioners need to know about working in the field of forensic anthropology'--Provided by publisher.
The theoretical and scientific foundations of forensic anthropology / C Clifford Boyd, Donna C Boyd -- Bias and objectivity in forensic anthropology theory and practice. Subjective with a capital S? Issues of objectivity in forensic anthropology / Allysha Powanda Winburn -- Navigating cognitive bias in forensic anthropology / Michael W Warren, Amanda N Friend, Michala K Stock -- Theoretically interesting / Soren Blau -- The theory and science behind biological profile and personal identification. From Blumenbach to Howells / Stephen Ousley, Richard L Jantz, Joseph T Hefner -- The application of theory in skeletal age estimation / Natalie R Langley, Beatrix Dudzik -- Theory and histological methods / Christian M Crowder, Deborrah C Pinto, Janna M Andronowski, Victoria M Dominguez -- Forensic applications of isotope landscapes ('isoscapes') / Lesley A Chesson, Brett J Tipple, James R Ehleringer, Todd Park, Eric J Bartelink -- Scientific foundation for interpretations of antemortem, perimortem, and postmortem processes. The anatomical basis for fracture repair / Donna C Boyd -- Theoretical foundation of child abuse / Jennifer C Love, Miriam E Soto Martinez -- Bone trauma analysis in a forensic setting / Hugh E Berryman, John F Berryman, Tiffany B Saul -- Thinking outside the box / John A Williams, Ronald W Davis -- The forensic anthropologist as broker for cross-disciplinary taphonomic research related to estimating the postmortem interval in medicolegal death investigations / Daniel J Wescott -- Interdisciplinary influences, legal ramifications, and future directions. Archaeological inference and its application to forensic anthropology / C Clifford Boyd, William W Baden -- Arrows of influence / John F Schweikart, Cheryl A Johnston -- Forensic anthropology, scientific evidence, and the law / Donna C Boyd, C Clifford Boyd -- Epilogue / C Clifford Boyd, Donna C Boyd.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Forensic Anthropology -- methods; Forensic anthropology -- Methodology; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; Forensic anthropology -- Methodology; Electronic booksl